Hegel's conscience - Moyar, Dean. (New York ; Oxford : Oxford University Press, 2011)
This text provides a new interpretation of the ethical theory of G.W.F. Hegel. The aim is not only to give a new interpretation for specialists in German Idealism, but also to provide an analysis that makes Hegel's ethics accessible for all scholars working in ethical and political philosophy.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Conscience; Ethics